Force analysis of a sprint canoe blade - Morgoch, D.; Tullis, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2011)
The motion of a sprint canoe blade through the water is extrapolated from video analysis of the paddle handle motion and used to approximate the forces acting on the blade throughout a stroke. Frame analysis of the video provides the displacement of the blade, and consequently the water velocity and angle of attack at both the top and bottom of the blade. Based on a quasi-steady approach, the relative velocities and angles of attack are used to approximate the lift and drag forces acting on the blade, which are then decomposed into propulsive and vertical forces. Lift forces on the blade contribute significantly to both propulsive and vertical forces. The different flows and forces in the three phases of the stroke: catch, draw, and exit, can be seen. The end of the catch phase experiences large propulsive and small upward vertical forces. During the draw phase there is a strong propulsive force, with evidence of a double peak. The vertical force steadily declines and becomes negative as the horizontal angle becomes greater than 90°, and reaches large negative values at the end of the draw. During the exit phase both the propulsive and vertical forces approach zero.